Cotreatment with lenvatinib and warfarin potassium caused prothrombin time prolongation. Issue 11 (10th July 2019) - Sasaki, Yoichi; Sakamori, Ryotaro; Yamada, Ryoko; Shigekawa, Minoru; Tahata, Yuki; Makino, Yuki; Nakabori, Tasuku; Kodama, Takahiro; Hikita, Hayato; Tatsumi, Tomohide; Takehara, Tetsuo
Abstract : Lenvatinib is approved as a standard systemic therapy for unresectable hepatocellular carcinoma (HCC) patients; however, experience with lenvatinib in clinical practice is insufficient. We present the case of a patient with advanced HCC whose prothrombin time – international normalized ratio (PT‐INR) was elevated after cotreatment with lenvatinib and warfarin potassium. The patient was a 26‐year‐old man with congenital abnormalities who had to take warfarin potassium because he had a mechanical heart valve. He was diagnosed with unresectable HCC at 24 years old and was treated by transcatheter arterial chemoembolization and transcatheter arterial infusion. After some interventional radiology treatments, lenvatinib was started. After 4 days of treatment with lenvatinib and warfarin potassium, his PT‐INR increased to 4.13, and the treatment had to be stopped. No changes were observed in other Child–Pugh score factors. The elevation in the PT‐INR after cotreatment with lenvatinib and warfarin potassium was thought to be caused by pharmacological effects of concurrent use or pharmacological sensitivity to warfarin potassium in this patient with liver dysfunction. The PT‐INR must be monitored when lenvatinib is given to advanced HCC patients taking warfarin potassium.